Study of vorticity and helicity distribution in advective flow with secondary structures - Evgrafova, Anna Valerievna; Levina, Galina Vladimirovna; Sukhanovskii, Andrey Nikolaevich (Computational Continuum Mechanics, 2013)
The distribution of vorticity and helicity in a stationary cylindrical fluid layer locally heated at its center is studied numerically and experimentally. Such localized heating leads to the generation of a large-scale flow in the form of a toroidal convective cell. In the heating area, small-scale secondary flows and local upward jets appear. The goal of this study is to investigate helicity and vorticity structures produced by the interaction between the shear flow and the upward jets. Formation and evolution of vortex structures in the boundary layer of advective flows are considered in detail. It is shown that the interaction of convective jets with the advective flow does not give rise to substantial non-zero mean helicities and the vertical component of vorticity.